The Effectiveness of The Sexual Violence Crimes Law (UU TPKS) in Protecting Women’s Human Rights: An Analysis of Gender Bias and Law Enforcement Challenges - Dovirullah Dovirullah; Tata Alfatur Rubbah; Fahrul Rossi; Aina Ersa (CLEAR: Criminal Law Review, 2025)
The development of criminal law in Indonesia has advanced notably with the enactment of Law Number 12 of 2022 on Criminal Acts of Sexual Violence (UU TPKS), marking a milestone in protecting female victims. Despite this progress, enforcement faces significant challenges, including cultural resistance, difficulties in evidence gathering, and a lack of gender sensitivity among law enforcement. This study analyzes the TPKS Law’s implementation concerning women's human rights and identifies structural and social barriers hindering justice for victims. It focuses on how the law has been applied in sexual violence cases and examines ongoing gender inequalities and human rights violations in practice. Using a juridical-sociological method with case studies of court decisions and interviews with victims, lawyers, and officials, the research draws on legal feminism and gender-based human rights theories. Initial results show that although the TPKS Law offers a progressive framework, patriarchal institutional practices obstruct real justice. The study recommends a more gender-responsive approach and comprehensive training for law enforcement to better safeguard women's rights. Perkembangan hukum pidana di Indonesia mengalami dinamika signifikan dengan diberlakukannya Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (UU TPKS), yang menjadi tonggak baru dalam perlindungan hukum bagi korban perempuan kekerasan seksual. Meski demikian, pelaksanaan UU TPKS masih menghadapi berbagai tantangan serius, seperti resistensi budaya, kesulitan dalam proses pembuktian, dan kurangnya perspektif gender di kalangan penegak hukum. Studi ini menganalisis pelaksanaan UU TPKS dalam konteks perlindungan hak asasi perempuan serta mengidentifikasi hambatan struktural dan sosial yang dihadapi korban dalam memperoleh keadilan. Fokus penelitian meliputi bagaimana UU TPKS diterapkan dalam menangani kasus kekerasan seksual terhadap perempuan dan bentuk-bentuk ketidaksetaraan gender serta pelanggaran HAM yang masih muncul dalam praktik penegakan hukum. Metode yang digunakan adalah yuridis-sosiologis dengan pendekatan studi kasus pada beberapa putusan pengadilan setelah penerapan UU TPKS serta wawancara dengan korban, penasihat hukum, dan aparat penegak hukum. Teori yang digunakan adalah feminisme hukum dan HAM berbasis gender. Temuan awal menunjukkan bahwa meskipun UU TPKS memberikan kerangka hukum progresif, hambatan institusional dan budaya patriarki masih menjadi penghalang utama dalam mencapai keadilan substantif bagi korban perempuan. Pendekatan hukum yang lebih responsif gender dan pelatihan bagi aparat penegak hukum sangat diperlukan untuk memastikan perlindungan hak perempuan secara menyeluruh.